OAT10/SLC22A13 Acts as a Renal Urate Re-Absorber: Clinico-Genetic and Functional Analyses With Pharmacological Impacts - Toyoda, Yu; Kawamura, Yusuke; Nakayama, Akiyoshi; Morimoto, Keito; Shimizu, Seiko; Tanahashi, Yuki; Tamura, Takashi; Kondo, Takaaki; Kato, Yasufumi; Ichida, Kimiyoshi; Suzuki, Hiroshi; Shinomiya, Nariyoshi; et al. (Frontiers in Pharmacology, 2022)
Dysfunctional missense variant of organic anion transporter 10 (OAT10/SLC22A13), rs117371763 (c.1129C>T; p.R377C), is associated with a lower susceptibility to gout. OAT10 is a urate transporter; however, its physiological role in urate handling remains unclear. We hypothesized that OAT10 could be a renal urate re-absorber that will be a new molecular target of urate-lowering therapy like urate transporter 1 (URAT1, a physiologically-important well-known renal urate re-absorber) and aimed to examine the effect of OAT10 dysfunction on renal urate handling. For this purpose, we conducted quantitative trait locus analyses of serum urate and fractional excretion of uric acid (FEUA) using samples obtained from 4,521 Japanese males. Moreover, we performed immunohistochemical and functional analyses to assess the molecular properties of OAT10 as a renal urate transporter and evaluated its potential interaction with urate-lowering drugs. Clinico-genetic analyses revealed that carriers with the dysfunctional OAT10 variant exhibited significantly lower serum urate levels and higher FEUA values than the non-carriers, indicating that dysfunction of OAT10 increases renal urate excretion. Given the results of functional assays and immunohistochemical analysis demonstrating the expression of human OAT10 in the apical side of renal proximal tubular cells, our data indicate that OAT10 is involved in the renal urate reabsorption in renal proximal tubules from urine. Additionally, we found that renal OAT10 inhibition might be involved in the urate-lowering effect of losartan and lesinurad which exhibit uricosuric effects; indeed, losartan, an approved drug, inhibits OAT10 more strongly than URAT1. Accordingly, OAT10 can be a novel potential molecular target for urate-lowering therapy.